Use of facebook as a media for developing student digital literacy competence - Budi Arif Fahrudin; Novan Ardy (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
The utilization of Facebook as a medium for developing students' digital literacy competence is an interesting research topic to explore in order to understand how Facebook can assist students in enhancing their digital literacy skills. The research employed a qualitative method with data collection through observation, interviews, and documentation. The findings of the study indicate that utilizing Facebook as a medium for developing digital literacy competence can help students improve their abilities to access, analyze, evaluate, and utilize information critically and creatively, while also serving as a platform for promotional purposes, such as promoting new student registrations, showcasing the school's profile, student achievements, school activities, and involving parents in the process, all while adhering to ethical guidelines and social media protocols. Students from MI Ma'arif NU Banjarsari in Ajibarang sub-district, Banyumas regency, need to ensure that every content they post on Facebook is accurate, relevant, and beneficial to the community. Additionally, MI Ma'arif NU Banjarsari should pay attention to copyright issues and respect others' privacy when uploading content on Facebook. Furthermore, students should comprehend the ethical and social implications of using digital media. Therefore, it is recommended that the utilization of Facebook as a medium for learning and promotion be conducted while considering the presented content, providing guidance and supervision to students, and fostering critical thinking skills and ethical behavior in using digital media.